HUBUNGAN DUKUNGAN PERAN KELUARGA DENGAN KELENGKAPAN IMUNISASI DASAR DPT ANAK DI DESA PAMOLAAN TANJUNG KABUPATEN SAMPANG TAHUN 2018 - Nur Imanah (Fakultas Ilmu Kesehatan, 2019)
The coverage of basic DPT immunization has decided 90% by government In fact, the coverage of basic DPT immunization in Pamolaan does not complete the target yet. The first DPT is around 85.8%, the second DPT is 71%, and the last DPT is 67.9%. Family’s support and role is one of factor that influences the completeness of basic DPT immunization. But until now, the correlation between family’s support and role with completeness of the basic DPT immunization for children doesn’t explain yet. This study was aimed to identify the correlation between family’s support and role with completeness of the basic DPT immunization. Design used in this study was cross sectional. The populations of the study were mother who has children at the age of six months to twelve months. Sample, enrolled using purposive sampling and total sample was fifty respondents who had been taken according to inclusion criteria. Independent variable was family’s support and role in completing basic DPT immunization. The dependent variable was the completeness of basic DPT immunization for children. Data were collected using Sperman and Chi square statistical test with significance level p < 0.05. Results showed that there is correlation between family’s support with completeness of the basic DPT immunization with correlation significant (p=0.045) and correlation coefficient (r=0.285). Then, there is correlation between family’s role with completeness of the basic DPT immunization with correlation significant (p=0.001) and contingency coefficient (C=0.474). It can be concluded that there are correlation between family’s support and role by showing a moderate correlation. So, family’s support and role can become reinforcing factor for mother to give DPT immunization for children but not the dominant factor.